Creatinine Trends to Detect Ibuprofen-Related Maturational Adverse Drug Events in Neonatal Life: A Simulation Study for the ELBW Newborn - van Donge, Tamara; Allegaert, Karel; Pfister, Marc; Smits, Anne; van den Anker, John (Frontiers in Pharmacology, 2021)
Background: Recognizing a change in serum creatinine concentrations is useful to detect a renal adverse drug reaction signal, also in extremely low birth weight (≤1000 g, ELBW) neonates. Assessing and characterizing the nephrotoxic side effects of drugs in ELBW neonates remain challenging due to the high variability in creatinine in this population. This study aims to investigate and quantify the impact of ibuprofen treatment on kidney function, reflected by serum creatinine. Method: A recently developed dynamical model for serum creatinine was used to simulate creatinine profiles for typical ELBW neonates with varying gestational and postnatal ages, whilst being exposed to ibuprofen treatment. Results: The extent of the increase of serum creatinine concentrations due to ibuprofen treatment is most profound during the first week of life. The difference in serum creatinine values between ibuprofen-exposed vs non-exposed neonates decreases with increasing postnatal age, independent of gestational age. Conclusion: The difference in serum creatinine concentrations between ibuprofen-exposed vs non-exposed neonates decreases with postnatal age, indicating an increased clearing capacity and resulting in a weak ibuprofen-related adverse drug reaction signal beyond early neonatal life.